Kajian Gas Removal System Dengan Memanfaatkan Second Ejector Dan Men-Stanby-Kan Liquid Ring Vacuum Pump Pada Sub Unit Darajat, UPJP Kamojang - Ammar Asof; Nurmiati Pasra; Taufik Hidayat (Sekolah Tinggi Teknik - PLN, 2016)
Gas Removal System at the Center for Geothermal Plant (PLTP) plays an important role as Non Condensable exhaust gas (NCG) in the condenser, to keep the condenser pressure remains low. Therefore steam expanded in the turbine will be condensed by water that is on the condenser.